Screening of onion (Allium cepa) genotypes to find out novel resistant source against purple blotch (Alternaria porri) - CHAUHAN, S S A; ISLAM, SABINA; PRASAD, LAKSHMAN; SINGH, SHRAWAN; ELLUR, R K; TOMAR, B S (The Indian Journal of Agricultural Sciences, 2023)
Purple blotch caused by Alternaria porri (Ellis) Cif., 1930 causes huge losses to bulb crop and seed crop of onion (Allium cepa L.). This is a major disease affecting successful onion production in majority of the onion growing areas. To identify resistant source against purple blotch, 34 onion genotypes with good marketable yield based on field evaluation trial in 2017 and allied species Pusa Soumya were screened under protected conditions during kharif, 2018 at insect proof net house facility of ICAR-Indian Agricultural Research Institute, New Delhi. The pure culture of Alternaria porri, isolated from infected leaf samples of onion crop raised under natural epiphytotic conditions during kharif, 2017. Highest change of disease severity index was observed between 1–2 weeks post inoculation (WPI) while highest disease severity index was recorded at 5 WPI suggesting that preventive measures must be employed as soon as disease symptoms appear in the field. The disease severity index ranged from 0.10–33.33 at 1 WPI, which increased to 9.33–89.33 at 5 WPI. The cultivated allied species Pusa Soumya was identified as novel resistance source with DSI value less than 10.0% at 5 WPI. Four genotypes exhibited moderately susceptible reaction, while 20 genotypes were susceptible and 10 genotypes were highly susceptible. The area under disease progress curve (AUDPC) value ranged from 22.33–240.17. Pusa Soumya had the lowest value and among onion lines Arka Kirtiman was found promising. Three onion genotypes had low relative AUDPC value and can effectively be utilized in resistance breeding programme. The average daily temperature between 20–25°C and relative humidity above 75% was found ideal for disease development.